Safety and Efficacy of Catheter Direct Thrombolysis in Management of Acute Iliofemoral Deep Vein Thrombosis: A Systematic Review - Ahmed Elbasty (Vascular Specialist International, 2017)
Purpose: Catheter direct thrombolysis (CDT) has been shown to be an effective treatment for deep venous thrombosis. The objective of the review is to improve safety and efficacy of the CDT by using ward based protocol, better able to predict complications and treatment outcome through monitoring of haemostatic parameters and clinical observation during thrombolysis procedure.